Kedudukan Penghubung Komisi Yudisial Wilayah Sumatera Selatan Dalam Struktur Ketatanegaraan RI - Yoshua Alexander; Nurhidayatuloh Nurhidayatuloh; Agus Ngadino; Abunawar Basyeban (Simbur Cahaya, 2019)
The aims of this research are to investigate the status of Regional Judicial Commission in Indonesia’s Constitution case South Sumatra Regional Judicial Commission and its role to maintain and oversee judges. The method used in this research is normative legal research. As a result, in fact the status of Regional Judicial Commission is a supporting organ under the Judicial Commission of Republic of Indonesia. It can be found in the 1945 Constitution Article 24B which gives authority to Judicial Commission to establish regional office. In addition, according to the Law No. 18 of 2011 that Judicial Commission enables to establish regional office in a certain province as its need. It is also stipulated in the Judicial Commission Regulation No. 1 of 2012 that the establishment of regional office aims to the accecibility for regional people in the mater of their report, the efectivity of trial monitoring, and socialization of the regional office in terms of maintainging and upholding of honor and dignity of the judges.